Faktor-Faktor Penentu Pengungkapan Sustainability Report: Bukti di Indonesia - Aji, Sapto Bayu (E-Jurnal Akuntansi; Vol 32 No 7 (2022), 2022)
The study examines the factors that influence the disclosure of the implementation of Corporate Social Responsibility (CSR). The purpose of this study is to explain the effect of profitability, liquidity, leverage, activity, company and company size on the disclosure of the implementation of social responsibility. The research sample is manufacturing companies listed on the Indonesia Stock Exchange from 2016 – 2019, which are 68 companies using purposive sampling technique. Data analysis was performed by statistical regression. The results of the study that the variables of profitability, liquidity, activity of the company and company size have a positive influence on the disclosure of the implementation of social responsibility, while leverage has a negative effect on the disclosure of the implementation of social responsibility. Keywords: Profitability; Likuidity; Leverage; Activity; Size; Sustainability Report.